The Ability of Group Counseling Guidance Services to Prevent Customary Behavior Using a Self-Counseling Approach - Niswatul Baroroh; Nurussakinah Daulay (Universitas Pendidikan Ganesha, 2023)
The characteristics of adolescents include a period of search for exploration so that adolescents act according to their wishes. However, sometimes adults perceive this as juvenile delinquency. This study aims to analyze the effectiveness of Group Guidance services using self-counseling techniques to reduce misconduct. Quantitative research type. This study used a quasi-experimental design with a nonequivalent control group research design. The total population of the study was 69 students in class XII MAN. The sampling technique used purposive sampling. The data collection techniques were literature study, interviews, questionnaires, and observation. The data collection instrument used a questionnaire sheet. Data analysis techniques using descriptive qualitative analysis, quantitative, and inferential statistics. The study's results proved a significant decrease in the pre and post-scores of the experimental group. In comparison, the results in the control group showed a significant decrease in pre and post-values. It was concluded that there was an insignificant decrease in inappropriate behavior if students were not given self-counseling techniques, while students who were given group guidance treatment with self-counseling techniques had a significant decrease.